(untitled) (Selecciones Matemáticas, 2021)
In this paper we study surfaces parameterized by lines of curvature. We obtain a characterization of a class of surfaces with planar lines of curvature, this characterization depend on certain holomorphic function. We present a class of surfaces with two family of planar lines of curvature, this class of surfaces includes the Dupin surfaces. Also, we give explicit examples.